Volumetric Analysis of Asphalt Concrete with Fly Ash Filler and Glass Powder Waste Filler against Seawater - Noor, Rusandi; Liana, Ulwiyah Wahdah Mufassirin; Nugraha, Bimantara Arya; Saputra, Muhammad Reza (JSE Journal of Science and Engineering, 2024)
This study investigated volumetric analysis on asphalt concrete mixtures containing fly ash filler and glass powder waste filler, focusing on the response to local inundation of seawater. This study investigated volumetric analysis on asphalt concrete mixtures containing fly ash filler and glass powder waste filler, focusing on response to local inundation of seawater which includes Stability, Flow, VIM, VMA, and VFB. In the 4-day seawater puddle model cycle, 12 specimens were made: 3 fly ash fillers, 3 glass powder waste fillers, and 3 normal asphalt, tested for 5 hours and 10 hours. This study explores the impact of fillers and inundation cycles on asphalt concrete characteristics. To realize the model of seawater puddles, in cylindrical specimens PVC retaining rings of the same diameter as the specimen (100 mm) are used tightly covered with silicone on the specimen surface. Filler with glass powder has low hygroscopic properties, which can help reduce moisture absorption in asphalt mixture beyond filler with fly ash. This can reduce the risk of changes in mechanical properties due to high water content. This study can provide an analysis of how well the asphalt mixture is able to withstand moisture and the extent to which glass powder filler and fly ash filler affect the absorbency of the mixture.